Customer preferences in selecting insurance company through insurance brokers (Eastgate Insurance Brokers Sdn.Bhd) / Fadzillah Elliani Md Azam - Md Azam, Fadzillah Elliani (Faculty of Business and Management, 2010)
A professional insurance broker deals with many insurers and has access to different types of policy wordings. They act for their clients and help them to decide what risks to insure, what types of cover are best and how much it should cost. Sometimes, clients are confusing in selecting insurance company since different insurance company offer different coverage to their clients. As such, this paper will identify the customer preferences in selecting insurance company through insurance brokers. Customers are referring to the several factors in selecting insurance company. There are the price of insurance product (premium), quality services of insurance provider (insurance company), coverage or benefits of insurance and the professionalism of brokers in handing with them. An insurance company may give the different coverage for the same policy than the others. So that, the customer should be well known and alert with the services given by each insurance company since most of insurance company offer the same policy. Therefore, customers have freely to get the services from insurance broker where broker is ready to receive instructions from his principal as to the nature of the risk or risks, the rate or rates of premium at which he wishes to insure, to communicate the material facts to the potential insurers and to obtain insurance for his principals in accordance with the principal’s instructions and on the best terms available. This research is conducted by using probability sampling which involved 50 respondents. From the finding, most of the respondents are prefer on coverage of insurance policy in selecting insurance company. As a conclusion on this research, all objectives have successfully been met. Based on the finding, some recommendation have been suggested in order to attract the customer using the insurance product.